Rainwater haversting system for landscape use in Gambang Campus, Universiti Malaysia Pahang (UMP) - Nur Atilya, Mahidan (2014)
Rainwater harvesting system is the collection of rainwater mostly via rooftop and stored in cistern for potable and non potable use. The purpose of this study is to find out rainwater quality harvested from rooftop and to obtain a rainwater harvesting system for collecting natural water. This research only considers determination of rainwater storage tank size by estimating rainwater supply and landscape water needs. Qualitative'assessment of rainwater collected via rooftop was determined using two selected roofing materials namely galvanized iron roofing sheet and clay tiles roofing sheet. The samples were collected directly from downpipe and the quality of rainwater was determined using standard method in, laboratory. The test included chemical oxygen demand (COD), biochemical oxygen demand (BOD), total suspended solids (TSS), ammoniacal nitrogen, eseherichia coli EColi) :and total coliforni. The study water quality classified as Class IV compared with National Water Quality Standard (NWQS). It was found that rainwater from galvanized iron roofing sheet was more polluted, followed b y clay tiles roofing sheet, The rainwater also is suitable to use for landscape irrigation, due to the water quality classification. For landscape watering in KKI Student Park, 50m 3 is the monthly maximum volume of water needed for irrigation.